2008
DOI: 10.2987/5672.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Fecundity and Survivorship of Six Copepod (Copepoda: Cyclopidae) Species, In Relation to Selection of Candidate Biological Control Agents Against Aedes aegypti

Abstract: ABSTRACT. The fecundity and survival of 6 copepod species were assessed under laboratory conditions in order to choose the best candidates to control the aquatic stages of dengue mosquitoes in the field. Females of all the 6 species (Mesocyclops aspericornis, Mesocyclops pehpeiensis, Mesocyclops woutersi, Mesocyclops thermocyclopoides, Mesocyclops ogunnus, and Megacyclops viridis) mated more than once. Multiple mating resulted in increased egg production. The reproductive ability and longevity varied among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 19 publications
1
15
2
1
Order By: Relevance
“…Moreover, the inter‐clutch periods in this study were longer than those observed in the five Mesocyclops species (1.3–1.5 days) in the experiments of Phong et al . (); but shorter than that observed in Mesocyclops leuckarti (3.9 days) reported by Hopp et al . ().…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Moreover, the inter‐clutch periods in this study were longer than those observed in the five Mesocyclops species (1.3–1.5 days) in the experiments of Phong et al . (); but shorter than that observed in Mesocyclops leuckarti (3.9 days) reported by Hopp et al . ().…”
Section: Discussioncontrasting
confidence: 51%
“…; Phong et al . ). Although, a high variability is often obtained in copepod offspring production by using females placed in totally similar conditions, we observed individual high variability occurred in terms of daily offspring production rate, spawning frequency and total number of offspring spawned during the lifetime in Mesocyclops sp..…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Widyastuti et al (2004) telah menguji M. aspericornis di beberapa tipe penampung air warga untuk menurunkan populasi jentik Aedes aegypti, keberhasilannya menurunkan populasi jentik A. aegypti sekitar 79,86-92,78%. Perlakuan dengan enam jenis copepodits diaplikasikan pada satu percobaan sebagai kontrol biologi Aedes aegypti, ternyata M. aspericornis memiliki tingkat predasi efektif untuk memotong siklus larva Aedes aegypti (Phong et al, 2008). Beberapa penelitian terbaru mencoba mengkombinasikan M. aspericornis dengan jenis predator Tilapia nilotika, mampu menurunkan jumlah larva Aedes aegypti dari instar I-IV sebesar 7,9% (Nasir et al, 2015), dengan demikian peranan M. aspericornis untuk menurunkan larva Aedes aegypti cukup efektif.…”
Section: P E N D a H U L U A Nunclassified